Assemble A Ku-Band frequency synthesizer - Ameri Mahabadi, H.; Moghavvemi, M. (2009)
This straightforward design shows how to assemble commercial components into a low-noise 14.4-to-15.5-GHz frequency synthesizer with 625-kHz tuning steps for digital microwave radio systems.